Development and psychometric validation of a joyfulness scale for Elementary School students in pickleball learning - Erafid Moardhika; Sapto Wibowo; Setiyo Hartoto; Taufiq Hidayat; Mochamad Ridwan; Advendi Kristiyandaru; Diane Soselisa (Sriwijaya Journal of Sport, 2026)
Research Problems: Joyfulness is an important affective component that plays a significant role in enhancing students’ engagement, motivation, and learning experiences in physical education. However, there is currently no instrument specifically designed to measure elementary school students’ joyfulness in the context of pickleball learning. The absence of a contextual and domain-specific instrument limits the accurate assessment of this affective construct, particularly within physical education in Indonesia. Research Objectives: This study aims to develop and psychometrically validate a joyfulness instrument for elementary school students in pickleball learning as a contextual and culturally appropriate measurement tool for Indonesian students. Methods: This study employed an instrument development design involving indicator construction, content validation, and construct validation. The instrument was developed based on five dimensions: (1) Emotional Joyfulness, (2) Enthusiasm and Excitement, (3) Satisfaction and Pride, (4) Comfort and Togetherness, and (5) Positive Motivation. The instrument consists of 30 Likert-scale items with four response options. Content validity was assessed by three experts using Aiken’s V. Construct validity was examined through Exploratory Factor Analysis (EFA) and second-order Confirmatory Factor Analysis (CFA) involving 330 elementary school students in grades 4–6. Results: Content validity analysis showed an Aiken’s V value of 0.90, indicating a very high level of expert agreement. EFA results confirmed a five-factor structure consistent with the proposed theoretical framework. The second-order CFA indicated a good model fit. In addition, the instrument demonstrated high reliability and met the criteria for both convergent and discriminant validity. Conclusion: The developed joyfulness instrument demonstrates adequate psychometric properties and can be used as a valid and reliable tool to measure elementary school students’ joyfulness in pickleball learning. This instrument has the potential to support the assessment of affective learning outcomes in physical education and contribute to the development of more enjoyable and meaningful learning experiences.